Characterization of Emergence of the Coulomb Blockade in a Pearl-Like DNA-AuNP Assembly - Tapio, Kosti; Toppari, J. Jussi (Journal of Self Assembly and Molecular Electronics, 2023)
Due to its superior self-assembly properties and vast functionalization pos- sibilities DNA has long been one of the most promising candidates for fabrication of nanoscale electrical components using molecular building blocks. There exist already many demonstrations on optical devices based on organizing metallic nanoparticles (NP) via DNA self-assembly, but despite the promises only few DNA based electrical devices or studies have been realized so far. Here we study the gold NP conjugated and metallized DNA TX-tile- structure, which we recently showed to exhibit the room temperature Coulomb blockade, the pre-requisition for a single electron transistor. The properties of the obtained Coulomb blockade are further characterized via the differential conductance measurements at temperatures ranging from 4.2 K to 10.2 K. The results show sharp blockade plateaus with varying threshold voltages, which yields further evidence of a gating effect by background charges. This strongly indicates that the DNA-NP assembly functions as a single electron transistor. Also, the additional growth of gold NPs and electrodes via chemical gold deposition process, needed to achieve the Coulomb blockade, is studied here in more details, yielding more insight to the process, and thus helping to realize better control of it.